Estudo fitoquímico e avaliação da atividade antioxidante de Combretum lanceolatum Pohl ex. Eichler (Combretaceae) - Oliveira, Gueybi Catherine Rondon Pereira (2019)
The genus Combretum, one of the most numerous in the Combretaceae family, records in Brazil approximately 22 species found in the Amazon, Caatinga, Cerrado, Atlantic Forest and Pantanal biomes. The phytochemical study of the genus Combretum demonstrates the occurrence mostly of triterpenes, followed by flavonoids, in addition to other secondary metabolite classes such as tannins. Chemical-pharmacological studies of Combretum lanceolatum by the LPQPN-UFMT research group on crude ethanolic extracts of flowers and leaves positively demonstrated antidiabetic and trypanocidal activity, possibly related to the presence of isolated quercetin flavonoids, 3-O- methyl quercetin, isoramnetine and dilenetin. In view of these encouraging results, it was important to continue the phytochemical investigation of the species, seeking to contribute to the chemical, biological and chemotaxonomic study through the crude ethanolic extract of flowers (EBEtOHF1) and the branches (EBEtOHG) submitted to liquid-liquid partition with increasing polarity solvents and chromatographic procedures, which allowed the isolation of nine secondary metabolites, identified by spectrometric and spectroscopic techniques, being these two flavonoids isoramnetine and tamarixetin, 3,3',4-tri-O-methylelagic, ellagic acid, quadranoside IV triterpenes, arjunglycoside II, and 22(R)-hydroxycycloart24-en-3-ol-derived cycloartan plus two free sugars α and β-glycopyranoside. With the exception of isoramnetin all other metabolites are being reported for the first time in the species. The evaluation of EBEtOHG antioxidant activity, branch ethyl acetate fraction (FGAcOEt) and branch butanolic fraction (FGBuOH) against the detection of potential free radical scavenger and cupric chelation showed satisfactory results, demonstrating proactivity in catalyzing the lipid peroxidation. The results obtained for iron chelation proved ineffective in the ability to chelate iron ions